SAFE ASPECTS OF TOURISM DEVELOPMENT IN THE CONVENTION OF THE COVID-19 PANDEMIC - Kyryliuk , I. M.; Chvertko, L.A. (The actual problems of regional economy development, 2021)
The purpose of the article is to substantiate the features, problems and mechanisms to ensure the safety of tourism in a pandemic COVID-19. During the study, dialectical and abstract-logical methods, methods of a systematic approach, comparison, observation, analysis, synthesis, induction, deduction, etc. were used. The information base of the study is domestic and international regulations, information from the United Nations World Tourism Organization, the Ministry of Culture and Tourism of the Republic of Turkey, scientific publications, Internet sources. A set of circumstances has been identified that indicate the need to address the issues of ensuring a sufficient level of security for tourism development in the context of the COVID-19 pandemic. The current state of the industry is analyzed and trends that affect the development of tourism during periods of quarantine or restrictive measures related to the spread of coronavirus disease are identified. The factors that allow to stimulate the growth of the level of security of tourism development are identified. The problems of security in tourism that hinder the tourism industry development are described. It is substantiated that the peculiarities of the functioning of the tourism industry in the context of the COVID-19 pandemic largely depend on the coordinated actions of governments on travel security, harmonization of safety protocols and effective communications, in the context of which state policy measures are implemented. It is proved that the need to provide preventive measures to prevent risks in the field of tourism is an important task of each individual country and international organizations. Measures, instructions and methods of tourist protection, which were identified by international organizations as necessary, are analyzed. The measures implemented by the countries of the world to minimize the negative consequences of the crisis in the tourism industry and ensure its further functioning and adaptation to the restrictive economic conditions of development are considered. The directions of ensuring the safety of the participants of the tourist market for the restoration of their tourist activity are outlined. The scientific novelty is to assess the threats to tourism and identify sustainable trends as a consequence of their direct impact in the context of the COVID-19 pandemic and justify the need to stimulate the development of security measures in the tourism industry based on current practical experience. The practical significance of the obtained results consists in the possibility of using theoretical conclusions and practical recommendations for the further development of tourism in the restrictive conditions associated with the spread of coronavirus disease.